Déwi Malêka: the Javanese Islam manuscript - Zakiyah Zakiyah (IAIN Salatiga, 2016)
This paper concerns on the Javanese Islam manuscript entitled Déwi Malêka Code Br.16 saved at the National Library of Republic Indonesia in Jakarta and Cod.Or 7562 preserved at the Library of Leiden University the Nether- lands. The objectives of this study are to describe the physical condition of the manuscripts and to examine the content of those two texts especially the Islamic and Javanese values. Data was collected using documentary research and analyzed using codicology, philology and Islamic studies. The finding of this research shows that these manuscripts tell about the story of Dèwi Maléka, a queen of Rum. From this story, it can be understood about the Islamic and Javanese values that are presented as questions and answers. In the last chapter of each text, there are some advises related to what should not be done by human being refereeing to the Javanese values. Artikel ini membahas manuskrip Islam Jawa berjudul Déwi Malêka kode Br.16 yang tersimpan di Perpustakaan Nasional Indonesia di Jakarta dan manuskrip dengan kode Cod.Or 7562 yang berada di Perpustakaan Universitas Leiden Belanda. Penelitian ini fokus pada deskripsi kondisi fisik naskah, dan isi dari dua teks tersebut, khususnya terkait dengan nilai-nilai Islam dan Jawa yang terkandung dalam teks. Data dikumpulkan dengan menggunakan s tudi dokumentasi dan dianalisis dengan bantuan ilmu filologi, kodikologi dan studi Islam. Temuan penelitian ini menunjukkan bahwa kedua naskah bercerita tentang Dèwi Maléka, ratu negeri Rum. Dari cerita yang dipaparkan dalam bentuk Tanya jawab dapat diketahui bahwa naskah ini berisi tentang nilai- nilai Islam dan Jawa. Pada bagian akhir teks terdapat nasehat terkait dengan apa-apa yang seharusnya tidak dilakukan oleh manusia. Nasehat-nasehat tersebut merujuk kepada nilai-nilai Jawa.